IDENTIFIKASI POSISI DAN KONTRIBUSI SEKTOR PERTANIAN DALAM PEREKONOMIAN DAERAH DI KABUPATEN TEMANGGUNG - Hendri Wibowo; Darsono Darsono; .Eka Dewi Nurjayanti (MEDIAGRO, 2016)
This study aims to determine the economic-sector and the agricultural sub-sector that become a basic sector/subsector, knowing the role changing of economic sectors and agricultural sub-sector in the future and determine the role changing of economy sector and agricultural sub-sector in Temanggung Regency. The research used descriptive analytical method using Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Shift Share (SS). The data that used are Gross Regional Domestic Product (GRDP) at constant prices 2000, from 2009 until 2013. Data obtained from BAPPEDA Temanggung Regency, Statistic Center Agency (BPS) Temanggung Regency and Statistic Center Agency (BPS) Central Java Province. The results showed that in the 2009-2013 period, there are  become Agricultural sector (1,68); Electricity, Gas and Water Supply (1,13); Transport and Communication sector (1,09); Financial, Ownership and Business Services sector (1,05); and Services sector (1,53) that become basic sector. on Agricultural sub-sector there are Non-Food Crops sub-sector (1,46) and Livestock and Products sub-sector (1,16) that become basic sub-sector. Based on DLQ value, Agricultural sector (8,29); Manufacturing Industry sector (1,03); Electry, Gas and Water Supply sector (2,87); Transport and Communication sector (1,21) and Services sector (1,77) are still become basic sector. In Agricultural sub-sector, Farm Food Crops sector (1,58); Fishery sector (80,39) are still become basic sub-sector. There are two economic sectors in Temanggung Regency that change the position in the future, Manufacture Industry sector change from non-basic sector (0,61) into basic sector (1,03); Financial, Ownership and Business Services sector change from basic sector (1,05) into non-basic sector (0,89). In Agricultural sub-sector, Farm Food Crops change from non-basic sub-sector (0,97) become basic sub-sector, Non Food Crop change from basis sub-sector (1,46) become basic subsector, Livestock and Products sub-sector change from basic sub-sector (1,16) become non basic sub-sector (0,21), and Fishery sub-sector change from non-basic sub-sector (0,21) become basic sub-sector (80,39). Factor that cause a position change in the Manufacturing Industry sector is the location. Factor that cause a position change in the Financial, Ownership and Business Services sector is the economic structure factor, while the factor that cause position change in the Agricurtural sub-sector is the location.   Keywords: Agricultural Sector, GRDP, LQ, Shift Share, Temanggung Regency